Modification of Automatic Semi System and Addition of Spin Polishing Function on Metalography Grinder Machine. (November 2019) - Susanti, N A; Zakiyya, H; Samani, M; Sakti, A M
Abstract: Grinding machines was available in the material testing laboratory of Unesa cannot be used for several reasons: there was no inlet and outlet fluids used during the process, the motor speed control has not been carried out and the grip specimen was not available. The result was the manufacture of semi-automatic workpiece clamping devices used a DC motor on polishing grinder. The dimensions of this tool was produced by length 500 mm x width 600 mm x height 570 mm used 1F Denso motor capacity of 12V 5A, with a maximum capacity of 50 mm long diameter of 40 mm. Polishing were influenced by the type of material and rotation's variation.